FOLK EXPRESSIONS AND THEIR ARTISTIC FEATURES IN THE WORKS OF TOGAY MURAD - Tursunova Muborak Nurmahmatova (Bright Mind Publishing, 2025)
This article highlights the features of using folk expressions in the works of Togay Murod and their stylistic and semantic functions in the literary text. The writer’s skillful use of expressions drawn from the language of the people enriches his artistic style, endows his works with national color and a folk spirit. The article analyzes the structural composition of the expressions, their role in character creation, and their significance for Uzbek linguistics. The results of the research justify the need for an in-depth study of the phraseological layer of Togay Murod’s work and further reveal the richness of the Uzbek literary language.
Keywords: Togay Murod, folk expressions, phraseology, artistic functions, national color, stylistic devices, Uzbek literary language, prose style.